10 Things for the Ideal Design RFP. (December 2016) - Calde, Steve
Abstract : RFPs can be an obstacle between a firm and the client, making it hard for both parties to evaluate the match. While it's important to request information from potential design partners that allows for side‐by‐side comparisons about capabilities, costs and approaches, you should also discern whether a firm is a good philosophical and culture fit. Ten recommendations for making a Request for Proposal (RFP) a highly effective tool for finding the perfect design and strategy partner.